2020
DOI: 10.7759/cureus.11649
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Different Risk Factors Among Adult Cardiac Patients at a Single Cardiac Center in Saudi Arabia

Abstract: Background Cardiovascular disease (CVD) has remained the leading cause of death in the last 15 years and is one of the main health problems in Saudi Arabia. Our study aims to assess the prevalence of different CVD risk factors and correlate them among King Faisal Cardiac Center patients in King Abdul-Aziz Medical City in Jeddah, Saudi Arabia. Methods We conducted a cross-sectional study using a convenient sampling technique. Data were collected by interviewing adult patients admitted to King Faisal Cardiac Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…In this study, the overall prevalence of dyslipidemia was 76.6% (95% CI: 72,181,0) using the NCEP ATP III criteria and the rate was almost comparable with the study reported from Iran, which indicated that 78.9% of cardiac patients suffered from dyslipidemia [ 24 ]. However, it is not consistent with the studies conducted in Saudi Arabia [ 25 ], Cameroon [ 1 ] and Gondar, Ethiopia [ 17 ], where the prevalence was 47.9%, 56.4% and 34%, respectively. Patient lifestyle, sample size, classification criteria for dyslipidemia, and genetic variability in the population may account for the differences described.…”
Section: Discussioncontrasting
confidence: 92%
“…In this study, the overall prevalence of dyslipidemia was 76.6% (95% CI: 72,181,0) using the NCEP ATP III criteria and the rate was almost comparable with the study reported from Iran, which indicated that 78.9% of cardiac patients suffered from dyslipidemia [ 24 ]. However, it is not consistent with the studies conducted in Saudi Arabia [ 25 ], Cameroon [ 1 ] and Gondar, Ethiopia [ 17 ], where the prevalence was 47.9%, 56.4% and 34%, respectively. Patient lifestyle, sample size, classification criteria for dyslipidemia, and genetic variability in the population may account for the differences described.…”
Section: Discussioncontrasting
confidence: 92%
“…dyslipidemia, hypertension, obesity, diabetes, smoking) are highly prevalent and are most often synchronous (more than three cardiovascular risk factors in almost half of the population) and the onset of cardiovascular disease is one to two decades younger in age [ 30 ]. Based on risk factors, it is estimated that a significant portion of the Saudi population will develop severe coronary events (myocardial infarction or coronary death) [ 31 ] or CVD [ 32 ] in the next 10 years. A gender-based approach might be appropriate in Saudi Arabia, where women seem to more often present with high risk CVD risk factors [ 33 ] and suffer from more adverse outcomes after surgery for CAD [ 34 ].…”
Section: Results - Consensus Statementsmentioning
confidence: 99%
“…The PURE-Saudi study revealed the alarming prevalence of CVD risk factors in the adult Saudi population; of 2047 participants, approximately 70% had low physical activity, half were obese, 34% followed an unhealthy diet, 32% had dyslipidemia, 30% were hypertensive, and 25% were diabetic. Current smoking, sadness/depression, anxiety and stress were also relatively prevalent in the Saudi population [ 32 , 107 ]. Gender-based approaches might be needed in Saudi Arabia seeing as women might have a higher predisposition to exhibit high risk for CVD compared to similarly aged men [ 33 , 108 ].…”
Section: Results - Consensus Statementsmentioning
confidence: 99%
“…Depression was assessed among cardiac patients in Jeddah and reported that 66.9% of patients had depression. [ 9 ] Even though, several studies have discussed this topic in different countries, there is a knowledge gap regarding this subject in Tabuk. Studies have been conducted in Saudi Arabia as well, but in different cities and of single-centre study.…”
Section: Introductionmentioning
confidence: 99%